Status and Threats of Slender Loris (Loris lydekkerianus) at Tiruchirappalli District, Tamil Nadu, India - Carlton R.; Daisy Caroline Mary A.; Griffith Michael G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Grey slender loris, Loris lydekkerianus is one of the least studied of all primates in India because of its elusiveness. A status survey is impertinent to conserve this endangered (IUCN) and Schedule I of the Wildlife (Protection) Act of India, 1972. Hence a survey of the Grey slender loris was undertaken to assess the status and threats of slender loris so as to formulate strategies of conservation. A survey was conducted from November 2019 to February 2020 at suburban and rural habitats of Tiruchirappalli. A weekly nocturnal survey was done, for assessing and identifying the status. Vehicle survey and foot survey was adopted depending on the access and topography of the terrain for the surveys. As a result of the study, we were able to record the presence of loris in all the four ranges. However, the number of sightings were few and out of the 10 sites, loris was recorded only in seven. The major threats were identified as habitat loss or the destruction of its habit and poaching activity. In addition to this slender lorises are illegally smuggled to supply a growing exotic pet trade. This implies that steps need to be taken to assure the protection and conservation of the species.